Notas en torno al análisis dramatúrgico de experiencias desiguales de corrupción a pequeña escala - Manchinelly Mota, Edgar Daniel (El Colegio de México, 2017)
In the last two decades, corruption has emerged as a relevant subject on a worldwide scale, because of its negative effects on the economy and State institutions, among other things. Research has focused on the macro aspects of corruption, emphasizing its causes and consequences. However, small-scale corruption has not been studied in such detail. This document proposes a theoretical-methodological framework for a dramaturgical analysis of small-scale corruption, with the aim of demonstrating that it is a stratified interaction. In this sense, corruption is an unequal experience for citizens, which depends on individuals’ social position.